2010
DOI: 10.1159/000306630
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Chronic Tinnitus in Assiut, Egypt

Abstract: Background and Aim: Few comprehensive epidemiological studies of the prevalence of tinnitus have been undertaken, and none has been carried out in Egypt. A community-based survey was conducted in the Assiut Governorate to estimate the prevalence of tinnitus, its associations with psychiatric disorders and its effect on the quality of life. Material and Methods: The study involved 8,484 subjects, 5,783 (68.2%) from the rural community and 2,701 (31.8%) from the urban community. Patients were identified from a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 47 publications
4
54
0
2
Order By: Relevance
“…Accordingly, our data are compatible with higher (severe) tinnitus rates among residents in municipalities with a relatively small population size. This is in agreement with a survey from China, showing a higher tinnitus prevalence in rural than in urban areas [18], although in Egypt the opposite was observed [22]. A few studies investigated the relationship between marital status and tinnitus, showing no significant difference [21,36].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Accordingly, our data are compatible with higher (severe) tinnitus rates among residents in municipalities with a relatively small population size. This is in agreement with a survey from China, showing a higher tinnitus prevalence in rural than in urban areas [18], although in Egypt the opposite was observed [22]. A few studies investigated the relationship between marital status and tinnitus, showing no significant difference [21,36].…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, only 20 previous studies from 14 countries reported information on adult tinnitus prevalence using surveys recorded at a national or sub-national level. Online supplementary table 1 (www.karger.com/doi/10.1159/000431376) shows the summary results from those surveys [5,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Prevalence of tinnitus in adults ranged between 5 and 30% and that of severe tinnitus from less than 1 to 7%.…”
Section: Introductionmentioning
confidence: 99%
“…3 The results of the study showed a prevalence of 10•1% among adults, with the tinnitus described as moderately annoying by 2•8% of respondents, severely annoying by 1•6%, and at a level that severely aff ected ability to lead a normal life by 0•5%. Results from studies in Egypt, 4 Japan, 5 and Nigeria, 6 indicate tinnitus prevalence is broadly similar in these countries to in Europe and the USA. The prevalence of troublesome tinnitus increases with age to 70 years; results of some studies show that it continues to increase thereafter, although others have shown it to diminish.…”
Section: Epidemiologymentioning
confidence: 89%
“…About 10-25% of the adult population has prolonged tinnitus (11)(12)(13)(14). 70-80% of individuals with tinnitus have significant hearing difficulties (15).…”
Section: Introductionmentioning
confidence: 99%